The Last Hurrah : An examination of the social change in Britain between the 1930's and the 1960's as depicted in Agatha Christie's Miss Marple novels - Läpinen, Ronni (My University, 2019)
This thesis discusses how the change in the British society and class system is reflected in three of Agatha Christie’s Miss Marple novels written in the period of four decades: The Murder at the Vicarage (1930), The Body in the Library (1942) and The Mirror Crack’d From Side to Side (1962). The theoretical approach applied to the thesis is New Historicism. The aim of New Historicism is to understand history through literature and literature through history. The thesis discusses how reliable a depiction texts such as Christie’s Miss Marple novels convey of the era they were written in. The results show that Christie’s Miss Marple novels are a reliable depiction of the era they were written in since they do not contradict any major historical phenomena of the time and present the social change that occurred during that period in accordance with the mainstream historical narratives. Nevertheless, Christie’s novels are not a neutral overview of the period but a commentary from the upper class perspective.
Keywords: New Historicism, social history, class, Britain